Thermodynamical analogies in the problems of stability of socio-economic systems functioning and optimal control - Demutskiy, V. P.; Pihnastyi, O. M. (Фізико-технічний інститут низьких температур ім. Б. І. Вєркіна НАН України, 2006)
Thermodynamical analogies in the problems of stability of socio-economic systems functioning and optimal control are considered.
Keywords: production line; PDE-model of production; PDE-model flow production; PDE production model